Application of differential quadrature and Newmark methods for dynamic response in pad concrete foundation covered by piezoelectric layer - Taherifar, Reza; Zareei, Seyed Alireza; Bidgoli, Mahmood Rabani; Kolahchi, Reza (Journal of computational and applied mathematics, 2021)
This article deals with the dynamic analysis in pad concrete foundation containing Silica nanoparticles (SiO2) subject to seismic load. The foundation is covered by a piezoelectric layer for smart control of the structure. The weight of the building by a column on the foundation is assumed with an external force at the middle of the structure. The foundation is located in soil medium which is modeled by spring elements. The Mori–Tanaka low is utilized for calculating the equivalent material characteristics of the concrete foundation. The structural damping of the structure is considered based on Kelvin–Voigt model. The concrete structure is modeled by thick plate and the governing equations are derived based on first order shear deformation theory (FSDT) utilizing Hamilton’s principle. Applying differential quadrature method (DQM) and Newmark method, the dynamic deflection is obtained. The effects of applied voltage to smart layer, volume percent and agglomeration of SiO2 nanoparticles, structural damping, soil medium and geometrical parameters of structure are shown on the dynamic deflection. Results indicate that with applying negative voltage, the dynamic deflection is reduced significantly. In addition, the SiO2 nanoparticles decreases the dynamic deflection of the concrete foundation. •Mathematical modeling of pad concrete foundation.•The pad concrete foundation is covered with a smart layer.•The pad concrete foundation is reinforced by SiO2 nanoparticles.•The structural damping of the structure is considered based on Kevin-Voigt model.•Applying DQM and Newmark method, the dynamic deflection is obtained.